Comparative assessment of prevalence of fibrinogen (-455)G>A gene polymorphism in teenagers from various populations of Eastern Siberia - A. Y. Senkina (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
This study was performed to establish prevalence of alleles of polymorphism (-455)G>A of в-chain of fibrinogen gene in Russian and Buryat populations of Eastern Siberia. We used blood database of children and teenagers of Russian and Buryat nationality. Genotyping was carried out by a standard PCR method. Frequency of allele A in Russian population was 28,0 %, in Buryat population - 23,7 %. There were no statistically significant ethnic differences between these samples.